A senior student's guide to Australian history - French, C. P. (Clive Polton), 1934- (Stanmore, N.S.W. : Cassell Australia, 1976)
Handbook for secondary students studying Australian history ; provides outline treatments and reading lists for twenty major themes, including "The Aborigines" (pp.104-110). Issues identified: origin of Aboriginal Australians, general features, social organization, history of Black-White relations.
Includes bibliographies.
Keywords: Australia. Historiology. Secondary school texts; History -- Methodology; Government policy - Assimilation; Government policy - Initial period and protectionism; Anthropology; Settlement and contacts - Colonisation; Race relations - Violent; History - Theory and criticism; Australia -- History; Australia